EXPANSIVE SOILS STABILIZATION WITH ADDITIONAL SAND (CASE STUDY : JATILUHUR HAMLET, GLGAH AGUNG VILLAGE, PURWOHARJO SUB-DISTRICT, BANYUWANGI DISTRICT): Stabilisasi Tanah Ekspansif Dengan Penambahan Pasir (Studi Kasus : Dusun Jatiluhur, Desa Glagahagung, Kecamatan Purwoharjo, Kabupaten Banyuwangi) 1 - Ridwansyah, Muhammad Ari; Ma'ruf, Mokhamad Farid; Putra, Paksitya Purnama (Universitas Jember, 2018)
Expansive soil is one of the global problems in the field of construction. In the United States, the estimated cost of damage to buildings and infrastructure due to expansive soils reaches 15 million per year (Far & Flint, 2016). While in the hamlet Jatiluhur, Glagahagung village, District Purwoharjo, Banyuwangi district expansive soils much damage the walls and floors of residences. Damage caused by this type of soil has high shrunken properties. In order to reduce these properties stabilization needs to be done. Stabilization in this research uses sand as the stabilizer. The addition of sand aims to reduce the ratio of clay cohesion properties, increase density values, reduce the potential for soil development and reduce soil permeability. The sand content used for stabilization is 15%, 20%, 25%, 30% and 35%. From the test results obtained the original soil has a liquid limit of 90.86%, plastic limit of 36.97% and plasticity index of 53.89%. Under the USCS classification system, the original soil belongs to the category of high plastic clay soil. From several classifications of the expansive soil development potential, the original soil is included in the ground with a high level of development. While the result of mixed soil testing is found that the greater the level of sand can reduce the properties of plasticity, moisture content, and soil development. Tanah ekspansif di desa Glagahagung, Kecamatan Purwoharjo, Kabupaten Banyuwangi banyak merusak dinding dan lantai rumah warga. Kerusakan diakibatkan karena tanah jenis ini memiliki sifat kembang susut tinggi. Guna mengurangi sifat tersebut perlu dilakukan stabilisasi. Stabilisasi dalam penelitian ini menggunakan pasir sebagai stabilitator. Penambahan pasir bertujuan untuk mengurangi rasio sifat kohesi lempung, meningkatkan nilai kepadatan, mengurangi potensi pengembangan tanah dan menurunkan permeabilitas tanah. Kadar pasir yang digunakan untuk stabilisasi sebesar 15%, 20%, 25%, 30% dan 35%. Dari hasil pengujian didapat tanah asli memiliki batas cair sebesar 90,86%, batas plastis sebesar 36,97% dan indeks plastisitas sebesar 53,89%. Berdasarkan sistem klasifikasi USCS, tanah asli termasuk dalam kategori tanah lempung plastisitas tinggi. Dari beberapa klasifikasi mengenai potensi pengembangan tanah ekspansif, tanah asli termasuk ke dalam tanah dengan tingkat pengembangan tinggi. Sedangkan hasil dari pengujian tanah campuran didapatkan bahwa semakin besar kadar pasir dapat mengurangi sifat plastisitas, kadar air, dan pengembangan tanah.